simplify each expression by combining like terms.

-7(n-2)+2(n+1)

1 answer

To simplify the expression -7(n-2) + 2(n+1), we distribute the -7 and 2:

-7 * n = -7n
-7 * -2 = 14

2 * n = 2n
2 * 1 = 2

Now, we can combine the like terms:

-7n + 14 + 2n + 2

Finally, we combine the terms:

-7n + 2n + 14 + 2

Simplifying further:

-5n + 16
Similar Questions
  1. Simplify the expression by combining any like terms.4y+6-2y-9=_____ (Simplify your answer. Do not​ factor.)
    1. answers icon 1 answer
  2. Simplify the algebraic expression by combining like terms.(Simplify your​ answer.) -5x^2+13x^2=
    1. answers icon 1 answer
    1. answers icon 1 answer
  3. Simplify the expression by combining like terms.7x-3+2x+6 A 12x B 5x + 9 C 9x + 3 D 9x - 3
    1. answers icon 15 answers
more similar questions